2016
DOI: 10.1007/s00442-016-3575-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens trigger top-down climate forcing on ecosystem dynamics

Abstract: ; Vollestad, L. Asbjorn; Stenseth, Nils C.; Ghil, Michael. 2016. Pathogens trigger top-down climate forcing on ecosystem dynamics. Oecologia, 181 (2). 519-532. 10.1007/s00442-016-3575-8 Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. Pathogens trigger top-down climate forcing on ecosystem dynamics AbstractEvaluatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 62 publications
0
11
1
Order By: Relevance
“…Climatic shifts are of growing concern, not least because the consequences of complex synergies with intensified threats may produce unexpected outcomes and ‘no analogue’ or ‘novel’ systems (Strayer, ; Acreman et al, ). For example, Edeline et al () have shown that a recent water temperature increase has had a significant impact on fish predator–prey interactions within a large temperate lake. Deciding how best to maintain or restore aquatic systems subjected to multiple stressors, including climate change, will challenge managers and planners, as discussed below.…”
Section: Threats To Freshwater Fishesmentioning
confidence: 99%
“…Climatic shifts are of growing concern, not least because the consequences of complex synergies with intensified threats may produce unexpected outcomes and ‘no analogue’ or ‘novel’ systems (Strayer, ; Acreman et al, ). For example, Edeline et al () have shown that a recent water temperature increase has had a significant impact on fish predator–prey interactions within a large temperate lake. Deciding how best to maintain or restore aquatic systems subjected to multiple stressors, including climate change, will challenge managers and planners, as discussed below.…”
Section: Threats To Freshwater Fishesmentioning
confidence: 99%
“…The seasonal variation of environmental drivers imposes its rhythms and thus phenological synchrony, where spatio-temporal fluctuations of different ecological patterns are locked in phase across different ecosystems [6][7][8]. A substantial body of literature documents that different populations are influenced by coherent environmental fluctuations (e.g., [2,3,[9][10][11][12][13][14]). For example, evaluating the effects of climate variation on the intraguild-predation structure of the fish population in the Windermere lake, Edeline et al [12] show that the pathogen-induced regime shift is temperature-controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change also has had wider impacts on the Windermere ecosystem. Expansion of a pathogen of European Perch into the lake has acted synergistically with warming to induce a regime shift within its European Perch-Northern Pike interaction, triggering a trophic cascade (Edeline et al 2016). Trophic levels have responded differently to warming such that Windermere's phytoplankton, zooplankton, and timing of European Perch spawning have become desynchronized (Thackeray et al 2013).…”
Section: Europementioning
confidence: 99%